Data, data everywhere, but little to use!. Issue 8 (2nd October 2017) - Oyelude, Adetoun A.
Abstract : Purpose: This edition of the column aims to expand the ideas presented in a poster of the same title exhibited at the IASSIST Conference held in April 2017 in Kansas, USA. Design/methodology/approach: It explores the fact that data are constantly being generated daily; however, the use of these data is limited because of its unavailability to the general public in forms or formats they need. Findings: Data are important to research because of their high information value, that is, value-added information that is critical for decision-making. Originality/value: Data come in many forms — census, statistics, research results, figures, graphs, interview transcriptions, journal entries, etc.